Re-engaged students' perceptions of mainstream and flexible learning environments – a 'semi-quantitative' approach. Issue 12 (2nd December 2019) - Welters, Riccardo; Lewthwaite, Brian; Thomas, Joseph; Wilson, Kimberley
ABSTRACT: Flexible Learning Options (FLOs) attempt to enable secondary school completion by young people for whom 'mainstream' schooling has not worked well. Despite their proliferation and the increased research attention to understanding the mechanisms at work within such programmes, quantitative methods have not been utilised to compare participants' perceptions of the learning environments of FLOs and mainstream schools. This study describes the development and application of a quantitative instrument to assess re-engaged Australian students' perceptions of an FLO relative to their previous (mainstream) schools. Findings indicate that, on average, young people rate the learning environment more highly at the FLO than at the mainstream school from which they disengaged, indicating that the learning environment of the FLO aligns more closely with the needs of its student cohort. However, bimodal results for some instrument items highlight that the learning environment is influential, but not necessarily a precondition of school disengagement or re-engagement. Implications of this study are considered, with attention to the complexities that mainstream schools and FLOs negotiate in creating effective learning environments for diverse young people.